Resolving marine dissolved organic phosphorus (DOP) composition in a coastal estuary. (28th July 2020) - Bell, Douglas W.; Pellechia, Perry J.; Ingall, Ellery D.; Benitez‐Nelson, Claudia R.
Abstract: A mechanistic understanding of dissolved organic phosphorus (DOP) utilization, and its role in the marine P cycle, requires knowledge of DOP molecular composition. In this study, a recently developed approach coupling electrodialysis and reverse osmosis with solution 31 P‐NMR analysis was used to examine DOP composition within a tidally dominated salt‐marsh estuary (North Inlet, South Carolina) over seasonal and tidal time frames. The isolation technique allowed for near complete recovery of the DOP pool (90% ± 13%; n = 12) with six broad compound classes quantified: phosphonates, phosphomonoesters, phosphodiesters, pyrophosphate, di‐ and tri‐phosphate nucleotides (nucleoPα ), and polyphosphate. Our results indicate that phosphomonoesters (ca. 61%) and phosphodiesters (ca. 31%) comprise the majority of the DOP pool, with relatively small contributions from pyrophosphates (ca. 4%), phosphonates (ca. 2%), nucleoPα (ca. 1%), and polyphosphates (ca. 1%). The study found no significant differences in DOP composition or concentration between tidal stages, despite significant tidal changes in dissolved organic nitrogen (DON):DOP stoichiometry. Significant seasonal variation was observed, with higher concentrations of phosphonates, nucleoPα, and monophosphates and lower phosphomonoester concentrations in Fall relative to all other seasons. We hypothesize that these seasonal variations reflect the balance between specific compound class seasonal production, lability, and local P demands associated with marine vs. terrestrial sources. Our results indicate that DOP composition exists at a dynamic equilibrium that is strongly conserved across diverse marine environments.